Organization of Knowledge Resources for The Development of a Virtual Assistant to Inform the Public About The SARS-Cov2 Pandemic - Katarzyna MLECZKO (Communications of International Proceedings, 2021)
This paper is the result of a practical project concerning the development of a virtual assistant to inform a selected social group about the situation related to the ongoing pandemic of the Covid-19 virus. The basis for proper communication between the user and the chatbot is adequately prepared and developed knowledge base integrating many different sources. The article presents the preparation process and the way of organizing the knowledge resources in the context of the previously adopted limiting criteria dictated, among others, by the needs of the users or the tool for creating a virtual assistant. The aim of building the chatbot was to limit disinformation and prevent the creation of information noise resulting from the abundance of information, facts, changes in the scope of restrictions or divergent opinions of various experts.
Keywords: Chatbot; virtual assistant; NLP; Coronavirus; covid; knowledge base; knowledge organization